(untitled) - Tahir Shah; Waqas Ahmed; Dr. Mahrukh Shakir (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The present research attempts to study the broad societal construction of women, which assigns them prescribed images and roles and shapes them accordingly, through analyzing the Victorian novel Tess of the D'Urbervilles. This novel by Thomas Hardy depicts the suffering of women in Victorian England, and the current qualitative study highlights the objectification of women from different aspects in the novel through textual analysis. The study applies the concept of objectification with feministic insight. The finding of the research concludes the sexual objectification of women on the basis of her gender and suggests that unless society and women themselves establish their existential rights as capable and autonomous human beings, they will not reach their full potential. It emphasizes how women's opposition to prevailing patriarchal notions gives them a new sense of self and opens up opportunities for them to defy social norms.